Potential of Selected Entomopathogenic Hyphomycetes for Controlling the Rice Pests, Sitophilus Oryzae (Coleoptera: Curculionidae) and Corcyra Cephalonica (Lepidoptera: Pyralidae) - Hendro Suyoko, Hendrawan Samodra (2003)
The rice weevil, Sitophilus oryzae (l.) and the rice moth, Corcyra cephalonica Stn.' are serious stored grain pests worldwide. They attack a wide variety of stored products and are the two important pests of stored rice. The use of entomopathogenic fungi (EF) is a novel approach to the control of insect pests of stored grains. The potential of dry conidia of three genera of EF, Beauveria bassiana, Metarhizium anisopliae and Paecilomyces fumosoroseus was examined in the laboratory against the adults of S. oryzae and the larvae of C. cephalonica. The pathogenicities of nine selected isolates of the EF (BbGc, BbPs, BbPc, MaOrMaj, MaSc, MaGmC, MaOrMan, MaPs, PfPp) to S. oryzae adults and C. cephalonica larvae were evaluated in the laboratory. All the isolates tested were pathogenic against S. oryzae adults and C, cephalonica larvae but pathogenicity varied among the isolates. Two isolates of B. bassiana (BbGc and BbPs) and one isolate of M. anisopliae (MaPs) were superior and caused high mortality against both these insects compared to other isolates. The median effective concentration (EC50) for isolates BbGc, BbPs and MaPs against C, cephalonica larvae were 1.238 x 106, 2.072 X 106, 1.775 X 106 conidia g-1 respectively. However, higher ECso values for these isolates were recorded against S. oryzae adult, namely 9.491 x 1 06, 1 .377 X 1 07, 1.120 x 107 conidia g-1 respectively. Thus, it can be concluded that C, cepha/onica larvae were more susceptible than S. oryzae adults to the three selected fungal isolates. The median lethal time (LT 50) at concentration 1 x 109 for these isolates against C. cepha/onica larvae were 3.5 d for BbGc, 3.6 d for BbPs and 3.5 d for MaPs and against S. oryzae adults were 3.1 d for BbGc, 3.3 d for BbPs and 2.5 d for MaPs.